What do the guidelines suggest for non-vitamin K antagonist oral anticoagulant use for stroke prevention in atrial fibrillation?. (22nd December 2016) - Shahid, Farhan; Shantsila, Eduard; Lip, Gregory Y.H.
Abstract : Vitamin K antagonists (VKAs, e.g. Warfarin) have been the cornerstone of stroke prevention in patients with non-valvular atrial fibrillation (AF) for well over 50 years, being highly efficacious in reducing stroke and mortality in this common arrhythmia. More recent data have shown the relative efficacy, safety, and convenience of the non-VKA oral anticoagulants (NOACs) over warfarin in patients with AF. Guidelines throughout Europe, America, and Canada acknowledge the value of NOACs and many recommend their use as first-line therapy, sometimes preferentially to warfarin. With the recent availability of reversal agents, there is little reason not to prescribe NOACs where appropriate. This article provides an overview of the current international guidelines with regard to NOAC use and highlights key areas by which emerging evidence may change the management of stroke prevention in patients with non-valvular AF.